2023
DOI: 10.1007/s42761-023-00180-7
|View full text |Cite
|
Sign up to set email alerts
|

Daily Sleep Quality and Support in Romantic Relationships: The Role of Negative Affect and Perspective-Taking

Abstract: Sleep is an important predictor of social functioning. However, questions remain about how impaired sleep-which is common and detrimental to affective and cognitive functions necessary for providing high quality support-is linked to both the provision and perception of support, especially at the daily level. We tested links between impaired sleep and provided and perceived support in romantic couples, and whether these links were mediated by negative affect and perspective-taking. In preregistered analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Moreover, we found no evidence that the prior night’s sleep was associated with next-day relationship stress or arguments. Findings are consistent with prior observations of links between hostile partner interactions and subsequent worse sleep (El-Sheikh & Rauer, 2013; Fillo et al, 2017; Hicks & Diamond, 2011), yet they contrast with adverse effects of poor sleep on the intensity and resolution of subsequent arguments (Gordon & Chen, 2014) and support provision to partners (Sell et al, 2023). Across studies, these findings suggest that poor sleep may be more closely associated with how partners approach subsequent conflict than with whether conflicts occur.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, we found no evidence that the prior night’s sleep was associated with next-day relationship stress or arguments. Findings are consistent with prior observations of links between hostile partner interactions and subsequent worse sleep (El-Sheikh & Rauer, 2013; Fillo et al, 2017; Hicks & Diamond, 2011), yet they contrast with adverse effects of poor sleep on the intensity and resolution of subsequent arguments (Gordon & Chen, 2014) and support provision to partners (Sell et al, 2023). Across studies, these findings suggest that poor sleep may be more closely associated with how partners approach subsequent conflict than with whether conflicts occur.…”
Section: Discussionsupporting
confidence: 88%
“…One possible explanation emerges from prior findings that relationship evaluations affect how partners interpret arguments (e.g., Johnson et al, 2018). Despite the negative cognitive and emotional effects of worse sleep (Sell et al, 2023), participants may have been less likely to register disagreements as overt arguments when their partners effectively pivoted away from tension after the disagreement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among a nationally representative US sample, adolescents with insufficient sleep (< 7 h) reported having poorer relationships with their mother and father than their counterparts with sufficient sleep (7–10 h) (Mueller et al, 2011 ). A recent 14-day diary study showed that poor sleep quality could predict next-day self-reported provision of support towards a partner and perceived support received from a partner, with such associations mediated by negative affect (Sell et al, 2023 ). It was concluded that sleep could influence the social relationship process, including the provision and perceived reception of support, partially through sleep’s influence on negative affect.…”
Section: Introductionmentioning
confidence: 99%